The History of Winemaking in Latin America and New Trends: Identity, Market, and Consumption - Lacoste, P (Springer International Publishing, 2024)
We explore the development of viticulture in Latin America through the three paradigms that prevailed throughout this development: the colonial paradigm, the French wine paradigm, and the Anglo-Saxon wine paradigm. This chapter will emphasize the rise and fall of wine production centers within the markets with the distinction of origin and the revaluation of mestizo wines thanks to the reevaluation of the historic vines of the territories, local laborers’ knowledge, and innovation in their exploration. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2024, Corrected Publication 2024.